2019
DOI: 10.1021/acs.est.9b01758
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Relative Humidity and Coexisting Soluble Iron on the OH-Initiated Heterogeneous Oxidation of Organophosphate Flame Retardants

Abstract: The current uncertainties in the reactivity and atmospheric persistence of particle-associated chemicals present a challenge for the prediction of long-range transport and deposition of emerging chemicals such as organophosphate flame retardants, which are ubiquitous in the global environment. Here, the OH-initiated heterogeneous oxidation kinetics of organophosphate flame retardants (OPFRs) coated on inert (NH4)2SO4 and redox-active FeSO4 particles were systematically determined as a function of relative humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 80 publications
2
27
0
Order By: Relevance
“…Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a). A significant negative correlation was observed between RH and particulate TBOEP (p b 0.05, Table S9), which is consistent with the finding that increased RH promotes TBOEP degradation via decreasing the viscosity of particle (Liu et al, 2014a;Liu et al, 2019). However, other hydrophilic OPEs including TCIPP and TCEP, the two important chlorinated OPEs with higher detection rates and measured concentrations in this study, did not possess a similar trend, indicating that the effect of RH may be obscured by other influence factors such as a more significant positive correlation with temperature of TCEP.…”
Section: Influence Factors Ofsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a). A significant negative correlation was observed between RH and particulate TBOEP (p b 0.05, Table S9), which is consistent with the finding that increased RH promotes TBOEP degradation via decreasing the viscosity of particle (Liu et al, 2014a;Liu et al, 2019). However, other hydrophilic OPEs including TCIPP and TCEP, the two important chlorinated OPEs with higher detection rates and measured concentrations in this study, did not possess a similar trend, indicating that the effect of RH may be obscured by other influence factors such as a more significant positive correlation with temperature of TCEP.…”
Section: Influence Factors Ofsupporting
confidence: 81%
“…Water (i.e., RH) can influence the OH-initiated heterogeneous oxidation of TBOEP via influencing the phase of particles, subsequently influence the mixing state and reactivity (Liu et al, 2014a;Liu et al, 2019). Furthermore, Li et al have revealed that RH could retard the reaction rate of •OH initiated heterogeneous oxidation of gaseous TCIPP and subsequently hindered the gaseous TCIPP degradation, implying the varied concentrations upon different humidity conditions (Li et al, 2017a).…”
Section: Influence Factors Ofmentioning
confidence: 99%
“…For example, levoglucosan and sucrose particles underwent an RH-induced phase transition from highly viscous to a less viscous state, with an increase of RH from 20 to 60% (37,38). Moreover, previous studies on organic particles (succinic acid and organophosphate esters) indicated that the heterogeneous OH oxidation kinetics increased by up to a factor of 41 at high-RH conditions (63 to 68%), compared to low-RH conditions (10 to 35%) due to a change in the particle viscosity with increased RH (39,40). Therefore, a similar RH-viscosity rationale may result in the RH effect in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…Organoiron chemistry is a critical chemical pathway in the atmospheric aqueous phase. However, this pathway has rarely been reported for the atmospheric isomerization of organics.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the form of iron, there are two main types of chemical reactions involving iron in the atmosphere: One is a complex photooxidation system composed of ionic iron and oxalate or other organic ligands. ,,, The other is the UV/Fenton system composed of ionic iron and H 2 O 2 . ,, ,, Both of these systems occur in the aqueous phase. Equations and are the process of generating superoxide by oxalate or organic ligands, and then the OH radicals are generated by hydrogen peroxide resulting from the subsequent chemistry of the superoxide from eq , thereby achieving the oxidative degradation of organics by the generated OH radicals. Equations – describe the mechanism of OH radical generation in both dark Fenton and photo-Fenton reactions At present, the photooxidation of atmospheric organics, such as isoprene, etc., has been studied, and some laboratories have even simulated the isomerization of stereochemistry for α-pinene under iron-modified mesoporous silicates . However, no attention has been paid to the isomerization of stereochemical organics in photo-Fenton reactions.…”
Section: Introductionmentioning
confidence: 99%